2021
DOI: 10.1002/ange.202114536
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐Independent Molecular Weight Determination of Polymers Based on a Truly Universal Calibration

Abstract: Diffusion-ordered NMR spectroscopy (DOSY) allows for accurate molecular weight calibration and determination that can be corrected for solvent influences. Polystyrene and poly(ethylene glycol) standards have been used to calibrate DOSY diffusion data for a variety of solvents, showing a high correlation of data when the bulk viscosity of the solvent is accounted for following the Stokes-Einstein equation. In this way, a type of universal calibration is introduced that allows for determinations of average mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…S3, ESI †) were observed at 2.92, 4.15, 3.00, and 4.32 ppm, respectively. The weight-average molecular weight of the polymer was evaluated by diffusion-ordered spectroscopy nuclear magnetic resonance (DOSY-NMR spectroscopy) to be ∼10 300 g mol −1 , according to technique recently reported by Junkers and coworkers 62 and with poly(ethylene glycol) as standard in DMSO-d 6 (Fig. S4, ESI †).…”
Section: Resultsmentioning
confidence: 99%
“…S3, ESI †) were observed at 2.92, 4.15, 3.00, and 4.32 ppm, respectively. The weight-average molecular weight of the polymer was evaluated by diffusion-ordered spectroscopy nuclear magnetic resonance (DOSY-NMR spectroscopy) to be ∼10 300 g mol −1 , according to technique recently reported by Junkers and coworkers 62 and with poly(ethylene glycol) as standard in DMSO-d 6 (Fig. S4, ESI †).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we have shown that even if standard calibration is applied to a very different type of polymer, a reasonable molecular weight estimate is obtained with an accuracy that at the very least rivals that of standard universal calibration SEC. 7 Most importantly, however, we have demonstrated that DOSY calibration is truly universal in the sense that no individual calibration of instruments is required. One calibration obtained in one lab is in principle applicable worldwide in a very broad molecular weight range from oligomers to millions of Da.…”
Section: Introductionmentioning
confidence: 88%
“…4–6 Diffusion-ordered spectroscopy (DOSY) has emerged as a promising technique for determining the molecular weight of polymers. 7,8 Based on many previous studies, we have demonstrated that DOSY is an accurate method for assessing the average molecular weights of polymers, competing favourably with standard SEC. Furthermore, we have shown that even if standard calibration is applied to a very different type of polymer, a reasonable molecular weight estimate is obtained with an accuracy that at the very least rivals that of standard universal calibration SEC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various methods have been developed to determine the molar mass such as size exclusion chromatography (SEC), , viscometry, and diffusion ordered nuclear magnetic resonance spectroscopy, among which SEC is the most prominent technique at present . Generally, the SEC system is equipped with a concentration-sensitive refractive index detector (SEC-RI).…”
Section: Introductionmentioning
confidence: 99%